Pengaruh permainan tradisional belompongan dan boi-boian terhadap gerak dasar manipulatif pada anak kelas 5 SDN 1 tunjang - Yogi Wardi; Elya Wibawa Syarifoeddin; Supriadin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The problem in this study is traditional fort and boi-boian games to increase motion, especially the basic manipulative movements of children, in this case researchers will focus more on the problem of basic manipulative movements of children with traditional games of begelompongan and boi-boian. This study aims to determine the influence of traditional games of lompong on manipulative motion. The research method used is a quantitative approach with an experimental design with One Sample Kolmogorov-Smirnov research type, with research instruments using throwing tests and ball catching tests. Data analysis using t test, normality test and homogeneity test with SPSS 24 For Windows assisted testing. The results of the study are based on a significant value of Xa 0.00 while the value of Xb 0.00 shows no significant difference between the pretest and posttest, this shows the ease of treatment in each variable paired sample test.